2018–2019 Precipitation Data - Mary Knapp (Kansas Agricultural Experiment Station Research Reports, 2020)
Precipitation data for Kansas Agricultural Experiment Stations and fields, 2018-2019.
Keywords: Kansas weather; Kansas precipitation; fertilizer